RESEARCH ON EFFICIENCY OF PRIMARY HEALTHCARE SERVICE OF SHANGHAI IN CHINA - Zhang, An; Xia, Wen; Yong, Bao (European Scientific Journal, ESJ, 2013)
Object: The article researches on efficiency of Shanghai Community Health Service (SCHS) and establishes production function of SCHS. Method: Establishing the production function of SCHS by Weighted Least Squares Estimation . Result: 1. Formulating the reasonable production function of SCHs based on Cobb: Douglas (C-D) function. 2. The article reveals SCHS production function with constant returns to scale. Conclusion: 1. Increasing human resource investment is a key factor for raising SCHS.2.Strenghten management and explore an efficient service model will improve SCHS level.